Rational Design of an Epstein-Barr Virus Vaccine Targeting the Receptor-Binding Site - Kanekiyo, Masaru; Bu, Wei; Joyce, M. Gordon; Meng, Geng; Whittle, James R.R.; Baxa, Ulrich; Yamamoto, Takuya; Narpala, Sandeep; Todd, John-Paul; Rao, Srinivas S.; McDermott, Adrian B.; Koup, Richard A.; et al. (Cell, 2015)
Epstein-Barr virus (EBV) represents a major global health problem. Though it is associated with infectious mononucleosis and ∼200,000 cancers annually worldwide, a vaccine is not available. The major target of immunity is EBV glycoprotein 350/220 (gp350) that mediates attachment to B cells through complement receptor 2 (CR2/CD21). Here, we created self-assembling nanoparticles that displayed different domains of gp350 in a symmetric array. By focusing presentation of the CR2-binding domain on nanoparticles, potent neutralizing antibodies were elicited in mice and non-human primates. The structurally designed nanoparticle vaccine increased neutralization 10- to 100-fold compared to soluble gp350 by targeting a functionally conserved site of vulnerability, improving vaccine-induced protection in a mouse model. This rational approach to EBV vaccine design elicited potent neutralizing antibody responses by arrayed presentation of a conserved viral entry domain, a strategy that can be applied to other viruses. [Display omitted] [Display omitted] •Self-assembling nanoparticles present the conserved gp350 receptor-binding domain•The nanoparticles elicit more potent neutralizing antibodies than soluble gp350•These neutralizing antibodies predominantly target the CR2-binding site on gp350•The nanoparticles elicit potent neutralizing antibodies in mice and non-human primates Structurally designed EBV vaccine candidates based on self-assembling nanoparticles elicit potent and durable virus-neutralizing antibodies that target the receptor-binding site on the viral envelope protein gp350, a site of vulnerability, serving as a template to develop an EBV vaccine and providing a basis for immunofocusing through rational vaccine design.